Sustainable assessment of metal industries for policy advice : the case of the Phillippines, Thailand, Indonesia and Viet Nam - Evans, Steve [et a;] (UNIDO ViennaAT, 2015)
Aims to provide a sustainable assessment of industries in an effort to provide an adequate analysis to inform policy making. Focuses on the metal industry in five ASEAN countries, viz., Indonesia, Malaysia, the Phillippines, Thailand and Viet Nam.